International Monetary Fund Annual Report 1955. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1955)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1955. The report highlights that in the course of 1954 and the first half of 1955, further considerable progress was made in the direction of free and less discriminatory trade. There was a continuation of the movement noted in the previous year, when steps were taken to relax the restrictions previously imposed for balance-of-payments reasons on imports, on currency transfers, and on dealings in foreign exchange.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet